2001
DOI: 10.1042/0264-6021:3550279
|View full text |Cite
|
Sign up to set email alerts
|

Genomic organization and characterization of splice variants of the human histamine H3 receptor

Abstract: In the present paper we report the genomic organization of the human histamine H3-receptor gene, which consists of four exons spanning 5.5 kb on chromosome 20. Using PCR, six alternative splice variants of the H3 receptor were cloned from human thalamus. These variants were found to be coexpressed in human brain, but their relative distribution varied in a region-specific manner. These isoforms displayed either a deletion in the putative second transmembrane domain (TM), H3(DeltaTM2, 431aa) or a variable delet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 19 publications
4
46
0
Order By: Relevance
“…This is also similar to the published K d values for histamine [47,48]. The results demonstrate, therefore, that this is a very fast association [46,49,50] and that both histamine and imetit showed the expected behaviour, in that they were able to increase the nFRET signal in a time-and concentration-dependent manner. Analysis of kinetics of receptors induced by different agonists in living cells showed that receptor modulation occurs very rapidly, and different agonists act differently on different receptor subtypes [51].…”
Section: Agonist-induced Activation Of Intramolecular H3 Receptor Fresupporting
confidence: 90%
“…This is also similar to the published K d values for histamine [47,48]. The results demonstrate, therefore, that this is a very fast association [46,49,50] and that both histamine and imetit showed the expected behaviour, in that they were able to increase the nFRET signal in a time-and concentration-dependent manner. Analysis of kinetics of receptors induced by different agonists in living cells showed that receptor modulation occurs very rapidly, and different agonists act differently on different receptor subtypes [51].…”
Section: Agonist-induced Activation Of Intramolecular H3 Receptor Fresupporting
confidence: 90%
“…10,11 HRH3 has also several unusual properties, demonstrating high constitutive activity [12][13][14] and a large number of functional isoforms resulting from alternative splicing. 15,16 HRH3 has been implicated to inhibit the release of monoamines and other neurotransmitters, presumably as a presynaptic receptor, [17][18][19] although direct evidence of the transmitter phenotype of neurons expressing HRH3 is still lacking. 1,20 HRH3 is also capable of forming dimers with dopamine receptors DRD1 and DRD2 and alter the signalling at these receptors, which further underlies the significance of HRH3 in the regulation of dopamine signalling.…”
Section: Introductionmentioning
confidence: 99%
“…In the human, H 3 R isoforms demonstrate differences in pharmacologic activity [33], [34], [35]. Many of these isoforms differ from the full length transcript by a variable-length deletion in the third IC loop.…”
Section: Resultsmentioning
confidence: 99%